Geochemical Fraction, Mobility And Bioavailability Of Lead In Unsaturated Soil Of Yogyakarta City, Indonesia - Saw Aung Zaw Aye; Heru Hendrayana; Doni Prakasa Eka Putra; Tsutomo Sato (Journal of Applied Geology, 2015)
Lead (Pb) is one of common heavy metals found inthe soil of urban environment. In Yogyakarta City,Indonesia, lead content in the soil was already reported by some researchers, however all of the report were only reveals the distribution of lead concentration in the soil. Therefore, this research paper aims to understand the geochemical fraction leadin the soil of Yogyakarta City and assess the mobility and bioavailability of lead release to the environment. The soil sampling location is selected on Kotagede District, representing the oldest urban area of Yogyakarta city. A shallow bore hole was drill until about 7 m below the surface and soil/sediments weresampled for each 1 m depth started from the surface. Six steps of sequential extraction procedures were carried out to assess the geochemical fraction of Pb for each of soil samples. The sequential extraction shows that the highest amount of Pb in thesoil of Yogyakarta City is found in amorphous ironoxide, crystalline iron oxide and non residual fraction form of Pb. Based on the results of geochemical fraction, the mobility factor of lead can be calculated and reveals low mobility factor range from 0.4 to 3.3%. The mobility of lead is decreased from the surface to the deeper soil, on the other hand the bioavailability of Pb calculated from exchangeable and carbonate fraction is also show low risk of bioavailability. Therefore, it can be concluded that although Pb concentration is high in non-residual fraction, Pb isin low risk condition due to its poor mobility and bioavailability. But, concern on lead contamination should be considered because if the concentration of Pb is enriched over the adsorption capacity of ironoxide, it can easily release to the environment and can impact to human in the future.Keywords: Yogyakarta city, Lead, Sequential extraction, Geochemical fraction